Modelling the Collective Mechanical Regulation of the Structure and Morphology of Epithelial Cell Layers - Khataee, Hamid; Fraser, Madeleine; Neufeld, Zoltan (Frontiers in Cell and Developmental Biology, 2022)
The morphology and function of epithelial sheets play an important role in healthy tissue development and cancer progression. The maintenance of structure of closely packed epithelial layers requires the coordination of various mechanical forces within the cells and others resulting from interactions with other cells and other tissues or substrates. However, a general model for the combination of mechanical properties which determine the cell shape and the overall structure of epithelial layers remains elusive. Here, we propose a computational model, based on the Cellular Potts Model, to study the interplay between mechanical properties of cells and dynamical transitions in epithelial structures and cell shapes. We map out phase diagrams as functions of cellular properties and the orientation of cell division. Monolayers of squamous, cuboidal, and columnar cells are found when the axis of cell proliferation is perpendicular to the substrate. Monolayer-to-multilayer transition is promoted via cell extrusion, depending on the mechanical properties of cells and the orientation of cell division. The results and model predictions are discussed in the context of experimental observations.